Microstructural analyses of the posterior cerebellar lobules in relapsing-onset multiple sclerosis and their implication in cognitive impairment. - Amandine Moroso; Aurélie Ruet; Delphine Lamargue-Hamel; Fanny Munsch; Mathilde Deloire; Pierrick Coupé; Julie Charré-Morin; Aurore Saubusse; Jean-Christophe Ouallet; Vincent Planche; Thomas Tourdias; Vincent Dousset; et al. (PLoS ONE, 2017)
Background The posterior cerebellar lobules seem to be the anatomical substrate of cognitive cerebellar processes, but their microstructural alterations in multiple sclerosis (MS) remain unclear. Objectives To correlate diffusion metrics in lobules VI to VIIIb in persons with clinically isolated syndrome (PwCIS) and in cognitively impaired persons with MS (CIPwMS) with their cognitive performances. Methods Sixty-nine patients (37 PwCIS, 32 CIPwMS) and 36 matched healthy subjects (HS) underwent 3T magnetic resonance imaging, including 3D T1-weighted and diffusion tensor imaging (DTI). Fractional anisotropy (FA) and mean diffusivity (MD) were calculated within each lobule and in the cerebellar peduncles. We investigated the correlations between cognitive outcomes and the diffusion parameters of cerebellar sub-structures and performed multiple linear regression analysis to predict cognitive disability. Results FA was generally lower and MD was higher in the cerebellum and specifically in the vermis Crus II, lobules VIIb and VIIIb in CIPwMS compared with PwCIS and HS. In hierarchical regression analyses, 31% of the working memory z score variance was explained by FA in the left lobule VI and in the left superior peduncle. Working memory was also associated with MD in the vermis Crus II. FA in the left lobule VI and right VIIIa predicted part of the information processing speed (IPS) z scores. Conclusion DTI indicators of cerebellar microstructural damage were associated with cognitive deficits in MS. Our results suggested that cerebellar lobular alterations have an impact on attention, working memory and IPS.